2014
DOI: 10.1002/marc.201400485
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Conductive Gold Nanowires in Confined Environment of Gold-Filled Polymer Nanotubes

Abstract: Continuous conductive gold nanofibers are prepared via the "tubes by fiber templates" process. First, poly(l-lactide) (PLLA)-stabilized gold nanoparticles (AuNP) with over 60 wt% gold are synthesized and characterized, including gel permeation chromatography coupled with a diode array detector. Subsequent electrospinning of these AuNP with template PLLA results in composite nanofibers featuring a high gold content of 57 wt%. Highly homogeneous gold nanowires are obtained after chemical vapor deposition of 345 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 29 publications
(51 reference statements)
0
1
0
Order By: Relevance
“…The most important advantage of the gas phase polymerization is the ability to coat even complex structures homogeneously. Microdevices, [ 36 ] nanotrenches, [ 37 ] fiber mats, [ 38,39 ] or open cell sponges [ 40 ] were coated successfully with PPX. Recently, we observed that porous materials such as sugar cubes can act as templates for the generation of ultralight PPX foams.…”
Section: Background Of Ppxmentioning
confidence: 99%
“…The most important advantage of the gas phase polymerization is the ability to coat even complex structures homogeneously. Microdevices, [ 36 ] nanotrenches, [ 37 ] fiber mats, [ 38,39 ] or open cell sponges [ 40 ] were coated successfully with PPX. Recently, we observed that porous materials such as sugar cubes can act as templates for the generation of ultralight PPX foams.…”
Section: Background Of Ppxmentioning
confidence: 99%